PLOT ELEMENTS ANALYSIS IN THE BEST OF ME NOVEL BY NICHOLAS SPARKS - Yeni Septina; Afrianto Afrianto (English Literature Study Program, Faculty of Arts and Education Universitas Teknokrat Indo, 2023)
The Best of Me tells about a young man named Dawson Cole with a background from a criminal family who falls in love with a woman from a noble and well-known family called Amanda Collier. Because there are some problem in it, their relationship ended tragically after they choose their own paths in life. The writer in this study analyzed the plot elements that contains in the novel and uses a structuralism approach based on plot theory from Richard Gill in a book entitled Mastering English Literature (1995). The objective in this research are to describe and identify the elements of plot contains in the novel entitled The Best of Me. The writer also apply a qualitative descriptive method because the data collection obtained through narration and dialogue in the novel. Gill (1995) explains that a complete and good plot has 5 important elements namely : the situation, disjunction, trajectory, proleptic events, and the last is reversal and discoveryKeywords:, plot, structuralism approach, The Best of Me